Spectral characteristics of visible light‐induced pigmentation and visible light protection factor. Issue 6 (26th June 2019) - Kohli, Indermeet; Nahhas, Amanda F.; Braunberger, Taylor L.; Chaowattanapanit, Suteeraporn; Mohammad, Tasneem F.; Nicholson, Cynthia L.; Kollias, Nikiforos; Lim, Henry W.; Hamzavi, Iltefat H.
Abstract: Solar radiation is a major contributor to the development of skin cancer. Recent studies have shown that visible light (VL), a major portion of solar spectrum, induces biologic effects on the skin. Ultraviolet filters in currently available broad‐spectrum sunscreens do not offer protection against VL. This study was designed to identify the spectral characteristics of the skin responses induced by VL, which can be utilized for time efficient in vivo VL testing. Thirty‐one subjects were irradiated with a light source emitting visible light with less than 0.5% long wavelength UVA1 (VL + UVA1, 370‐700 nm), and 41 subjects were irradiated with pure visible light (pure VL, 400‐700 nm). Assessments including clinical photography, investigator's global assessment of pigmentation and erythema, and diffuse reflectance spectroscopy (DRS) performed immediately and seven days after irradiation. Clinical and spectroscopic data showed that VL + UVA1 spectral output induced significantly darker and persistent skin responses as compared to those induced by pure VL. Spectroscopic signatures of skin responses induced by both radiation sources were identified. The signatures were found to be specific to the radiation source and time of collection. A method to evaluate VL protection factor, using quantitative information from the spectral signatures obtained, was proposed.